Neo‐sex chromosome evolution and phenotypic differentiation across an elevational gradient in horned larks (Eremophila alpestris). Issue 6 (31st January 2022) - Shakya, Subir B.; Wang‐Claypool, Cynthia Y.; Cicero, Carla; Bowie, Rauri C. K.; Mason, Nicholas A.
Abstract: Genetic structure and phenotypic variation among populations are affected by both geographic distance and environmental variation across species' distributions. Understanding the relative contributions of isolation by distance (IBD) and isolation by environment (IBE) is important for elucidating population dynamics across habitats and ecological gradients. In this study, we compared phenotypic and genetic variation among Horned Lark ( Eremophila alpestris ) populations from 10 sites encompassing an elevational gradient from low‐elevation desert scrub in Death Valley (285 a.s.l.) to high‐elevation meadows in the White Mountains of the Sierra Nevada of California (greater than 3000 m a.s.l.). Using a ddRAD data set of 28, 474 SNPs aligned to a high‐quality reference genome, we compared genetic structure with elevational, environmental, and spatial distance to quantify how different aspects of the landscape drive genomic and phenotypic differentiation in Horned Larks. We found larger‐bodied birds were associated with sites that had less seasonality and higher annual precipitation, and longer spurs occurred in soils with more clay and silt content, less sand, and finer fragments. Larks have large neo‐sex chromosomes, and we found that associations with elevation and environmental variation were much stronger among neo‐sex chromosomes compared to autosomes. Furthermore, we found that putative chromosomal translocations, fusions, and inversions were associated with elevation and may underlie local adaptation across an elevational gradient in Horned Larks. Our results suggest that genetic variation in Horned Larks is affected more by IBD than IBE, but specific phenotypes and genomic regions—particually on neo‐sex chromosomes—bear stronger associations with the environment.